Keamanan Dalam Electronic Commerce - Andre Michael Ricky Wajong; Carolina Rizki Putri (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The objective of this paper is to give information and understanding about security threat that could happen in security system in e-commerce. The approach used is how the transaction system is, how the security is applied, and also the possible security threat in e-commerce. The result of this research is that there are still gaps in e-commerce. It is hoped that the business actors will be more realized about the security importance and more aware about the possible threat.